Implementasi Model Pembelajaran Inkuiri dalam Meningkatkan Pemahaman Konsep Sains pada Siswa Sekolah Dasar Negeri 101930 Perbaungan - Yeshi Anggreini Hutabarat; Layil Safitri; Thessa Herdyana (Medan Resource Center, 2026)
This study was conducted in response to the need for more student-centered instructional approaches to improve elementary school students' understanding of science concepts. It investigates how the inquiry learning model was implemented in science instruction and examines its impact on fourth-grade students' conceptual understanding at SD Negeri 101930 Perbaungan. This research employed a descriptive qualitative approach involving 14 fourth-grade students as the unit of analysis. Data were collected through classroom observations supported by pre-test and post-test assessments, in-depth interviews with the classroom teacher, and documentation of learning activities and relevant written records. The findings demonstrate that the inquiry learning model was implemented effectively and significantly enhanced students' understanding of science concepts by promoting active exploration, questioning, investigation, and evidence-based reasoning. Students showed greater engagement throughout the learning process, which was reflected in the improvement of the class average score from 58.57 before the intervention to 84.71 after the implementation, with classical learning mastery increasing to 100%. These findings indicate that the inquiry learning model constitutes an effective instructional strategy for strengthening science concept understanding and fostering meaningful learning experiences among elementary school students.